Ecology-Based Islamic Counseling: A Dynamyc Study of Forest Conservation Actors on The Slopes of Mount Lamongan, Lumajang - Hoirina Ramadhanti; Bambang Subahri (Counselia, 2026)
This article examines forest conservation practices on the slopes of Mount Lamongan, Lumajang Regency, which are taking place amidst ecological pressures such as forest fires, land degradation, and increasing exploitation of natural resources. Amidst these conditions, community-based and individual forest conservation actors have emerged, facing not only technical environmental challenges but also complex psychological, social, and spiritual dynamics. This demonstrates that environmental conservation is a socio-religious practice that demands mental resilience, social legitimacy, and sustained religious meaning. Theoretically, this article combines the Islamic counseling concept developed by Abu Zaid al-Balkhi, particularly the notion of mental health and the balance between psychological, moral, and spiritual dimensions, with Peter L. Berger's social construction theory. This integration of the two perspectives is used to understand forest conservation as a social reality that is constructed, institutionalized, and religiously interpreted by its practitioners. This research employed a qualitative approach with a case study approach. The research location was in Klakah and Ranuyoso Districts, Lumajang Regency. Data were collected through in-depth interviews, field observations, and documentation, with informants selected purposively from forest conservation practitioners, religious leaders, journalists, and the local community. Data validity was maintained through triangulation of sources and techniques. The research results show three main conclusions: first, forest conservation actors experience interrelated psychological, social, and spiritual dynamics; second, Islamic values are interpreted as an ethical and spiritual foundation in conservation practices; and third, ecologically based Islamic counseling is relevant as a holistic mentoring model for the sustainability of community-based forest conservation.